Comorbidities of COVID-19 patients associated with mortality at the Baubau Regional Public Hospital, South East Sulawesi - Mustiqawati, Evi; Yolandari, Sri; Nurwanti, Ratih; Sapril, Sapril (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that cause coronavirus disease 2019 (COVID-19) has become a global pandemic. Until November 30th, 2020, World Health Organization (WHO) confirmed 61,869,330 positive cases with 1,448,896 deaths (CFR 2.3%). Some comorbidities are associated with the COVID-19 mortality. This study aimed to investigate risk factors of the COVID-19 mortality at the Baubau Regional Public Hospital, Sout East Sulawesi. It was a cross-sectional study with a retrospective analysis involving 81 COVID-19 patients. Purposive sampling was applied in this study. Chi-square analysis was conducted to calculate odd ratio (OR). The result showed that in the period from January to September 2021, 30 COVID-19 patients died consisting of 20 male and 10 female. Most of the patients died were >45 yo and only 4 patients died were <45 yo. Among the patients died, 11 patients had hypertension, 12 patients had type 2 diabetes mellitus (DM), 4 patients had pulmonary TB and 3 patients had dyspepsia. Further analysis showed that hypertension (OR=6.803; 95%CI: 1.925-24.038; p=0.002) and dyspepsia (OR=0.222; 95%CI: 0.059-0.838; p=0.016) were significantly associated with the COVID-19 mortality, whereas type 2 DM (OR=1.123; 95%CI: 0.445-2.832; p=0.495) and pulmonary TB (OR=0.559; 95%CI: 0.059-0.838; p=0.270) were not. In conclusion, hypertension is risk factor, whereas dyspepsia is protective factor of COVID-19 mortality.